Improving Patient Well-Being as a Broader Perspective in Dentistry - Arden Mills; Yuli Berlin-Broner; Liran Levin (Elsevier, 2023)
ABSTRACT: Patient well-being encompasses the physical, mental, psychological, and social health of an individual. To adequately treat an individual and increase their quality of life, whole-person, patient-centred care needs to be utilised. This review aims to concisely summarise ways to improve patients' well-being through and in dentistry. Oral health is tied to one's quality of life through oral function, overall health, self-perception, social acceptance, and social interaction. These relationships demonstrate the importance of utilising oral health to increase patient quality of life, unify health professions in patient treatment, use preventative medicine, and empower patients about their health. To do so, the dental profession can increase the scope of practice to provide preventative health screening and education on general health, have more open communication, collaborate with other health care professionals, and have broader consultations. This will allow for better continuity of care and shift the focus of treatment to the whole person instead of a symptom. Whilst there are barriers that need to be resolved and cost feasibility requires more exploration, the potential benefit to patients is apparent.